2011
DOI: 10.1038/ejhg.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Peutz–Jeghers syndrome and family planning: the attitude towards prenatal diagnosis and pre-implantation genetic diagnosis

Abstract: Peutz-Jeghers syndrome (PJS) is a hereditary disorder caused by LKB1 gene mutations, and is associated with considerable morbidity and decreased life expectancy. This study was conducted to assess the attitude of PJS patients towards family planning, prenatal diagnosis (PND) and pregnancy termination, and pre-implantation genetic diagnosis (PGD). In a crosssectional study, 61 adult PJS patients were asked to complete a questionnaire concerning genetic testing, family planning, PND and PGD. The questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…We anticipate that many more would have accessed this option had the parents been of reproductive age at the point of receiving the diagnosis. Accurate genetic diagnosis of developmental disorders empowers individuals to make informed and value-based reproductive decisions, highlighting the importance of a diagnosis for family planning purposes 23,24 . For many participants (53%), receiving a diagnosis meant they met the eligibility criteria for further research studies and subsequent successful recruitment suggests that they had a positive perception of genetic research following their involvement in the DDD study.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that many more would have accessed this option had the parents been of reproductive age at the point of receiving the diagnosis. Accurate genetic diagnosis of developmental disorders empowers individuals to make informed and value-based reproductive decisions, highlighting the importance of a diagnosis for family planning purposes 23,24 . For many participants (53%), receiving a diagnosis meant they met the eligibility criteria for further research studies and subsequent successful recruitment suggests that they had a positive perception of genetic research following their involvement in the DDD study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prenatal diagnosis did not affect their intention to have children. The attitude towards prenatal diagnosis of PJS has been evaluated in a recent Dutch study [ 16 ], in which 44% of PJS patients indicated that PJS had not influenced their desire to have children, and 38% of respondents would not consider termination of pregnancy after prenatal diagnosis. Moreover, Woo A et al [ 17 ] found that 40% of patients with PJS reported they had altered reproductive life choices based on their diagnosis of PJS and that 33% of participants were reluctant to have children due to PJS.…”
Section: Discussionmentioning
confidence: 99%
“…This form of testing can be performed following in vitro fertilization, and only embryos without hereditary mutation are implanted [ 18 ]. Indeed in van Lier’s study [ 16 ], 52% of PJS patients accepted the use of PGD. Moreover, in a study examining the attitude of couples towards genetic testing options for various genetic disorders, 66% of couples preferred PGD over PND for the diagnostic testing of a possible future pregnancy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available researches on the determinants of PGTs have looked at (1) the attitudes of women and their partners, [7][8][9][10][11][12] (2) religious beliefs and women's attitudes towards termination of pregnancy, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and (3) women's racial-ethnic background. [32][33][34][35][36] From a cohort study of Italian women at risk because of advanced maternal age, the key determinant factor which influenced choice regarding amniocentesis was the preexisting view that the women had towards such a procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Available researches on the determinants of PGTs have looked at (1) the attitudes of women and their partners, (2) religious beliefs and women's attitudes towards termination of pregnancy, and (3) women's racial‐ethnic background …”
Section: Introductionmentioning
confidence: 99%